Chemical and Molecular Characterization of Three Plant Species from Lamiaceae that Grow in Syria: Chemical and Molecular Characterization of Medicinal Plants (Biological Sciences - PJSIR, 2024)
The chemical composition of the essential oils extracted from three medicinal plant species that grow in Syria, namely Thymus syriacus Boiss., Origanum syriacum L. and Thymbra spicata L., was  identified by GC-MS. Results showed that T. syriacus oil contained 27 compounds, T. spicata oil contained 39 compounds and O. syriacum oil contained 33 compounds. Thymol was the most abundant component in the three species. Monterpenes and sesquiterpes were the chemical markers for those species and may be considered as general chemical markers for all species belonging to Lamiaceae family regardless of their genus. Inter-Simple Sequence Repeat (ISSR) analysis used to evaluate the genetic variation between the three species showed a close genetic relationship between T. syriacus and T. spicata. Overall, results, indicated that it is possible to discriminate between the three plant species based on both of their chemical composition and ISSR markers.